Study Of Consumer Protection Law Between Patients And Doctors - Amru Rahman (International Asia Of Law and Money Laundering (IAML), 2022)
Patients as parties who use health services in conjunction with health service providers are domiciled as consumers. Consumer Protection Act No.8 of 1999 does not provide specific protection for patients, even almost all of the material does not touch or cannot be applied in providing protection for users of health services, in addition, legislation in the field of health as a special regulation referred to by law- the Consumer Protection Act turns out that the substance of consumer protection is not regulated at all and even points back to the applicable general law, namely the Criminal Code and the Civil Code through criminal charges and / or civil suits that still use the principle of responsibility based on errors that must be proven so as to place consumers of Health.